ANALYSIS OF TRANSFORMATIONAL LEADERSHIP RELATIONSHIPS, WORK MOTIVATION, AND EMPLOYEE PERFORMANCE IN HEALTHCARE FACILITIES - Rosalina Cesilia; Vip Paramarta; Alexandra DeSousa Guterres (RADJA PUBLIKA, 2025)
Transformational leadership has become a crucial factor in enhancing work motivation and employee performance, particularly in healthcare facilities. This study aims to analyze the relationship between transformational leadership, work motivation, and employee performance using a literature review approach. The research method employed is a literature review of various academic sources related to the concept of transformational leadership, factors influencing work motivation, and its impact on employee performance in the healthcare sector. The analysis results indicate that transformational leadership, characterized by inspiration, idealized influence, intellectual stimulation, and individualized consideration, significantly contributes to improving motivation and employee performance. Leaders who encourage innovation, provide emotional support, and create a positive work environment can enhance job satisfaction and productivity among healthcare workers. The implications of this study highlight the importance of developing transformational leadership as a strategy to improve the quality of healthcare services.